THE EFFECT OF THE PICTORIAL NUMERIC CARD MEDIA TOWARD IMPROVEMENT OF THE SUMMATION COMPUTATION ABILITY FOR STUDENT WITH INTELLECTUAL DISSABILITY - Isna Nur Hikmah; Usep Kustiawan (Department of Special Education, 2016)
The reseach’s purpose was to analyze the effect of picture numeric card media toward improvement of the summation computation ability for student with intellectual disability of grade IV in SDLB. Data collected was analyzed with experiment technique and single subject research A-B design. Research result showed that: after being analyzed between condition overlap persentase was 0%. Thus, it could be concluded that there was effect of pictorial numeric card media toward summation computation ability of student with intellectual disability